Serial Killer’s Psychological Profile Investigation From Fbi Point Of View As Seen In Thomas Harris’s Silence Of The Lambs - Fandri Irawan Fandri Irawan; Andy Amirudin Andy Amirudin (Fakultas Sastra Universitas Ekasakti, 2025)
This study explores the FBI’s psychological profiling of serial killers as portrayed in Thomas Harris’s The Silence of the Lambs, focusing on the methods used to identify and understand psychopaths, especially through the interactions between Clarice Starling and Dr. Hannibal Lecter. Utilizing criminal psychology theory and a qualitative textual analysis of the novel, the research examines how offender behavior, motivations, and mental disorders inform profiling. Findings highlight the FBI’s detailed investigative process, the serial killer’s psychological manipulation to mislead investigators, and the critical role of the psychological profiler in penetrating the psychopath’s mindset to guide the investigation, revealing the complex interplay between profilers and criminals in solving difficult cases.